Confeccionando aplicativos em física: uma abordagem do Geogebra acerca das Leis de Newton - Luiz, Fábio Ferreira (2015)
The content of this dissertation intends to investigate the acceptance of Information and Communication Technology - ICT, linked to curriculum syllabus in physics in the state of Rio de Janeiro, more precisely the second quarter of the classes of first year of high school. Built with the help of free software called Geogebra, a set of applications that help a physics professor at the task of building competencies about Newton's Laws. Applications were divided in two parts: first, applets that allow for manipulation and vector operation. Subsequently, applets that simulate conditions for implementation of the three laws of Newton. This educational product was applied in two groups of first year high school CIEP 223 - Olympio Marques dos Santos, about 30 students manipulated the applets and decided exercises using the computer device. Another 30 students decided, the same exercises without the aid applets. We obtained, for students who have used the applets, an improvement in their income, which allows us to verify that the applets came the student body to a teaching/learning more aligned to its current technological reality.